Supramolecular soft materials and structural studies of a series of BTA and pyridine-dicarboxamide derivatives with various d-metal ions - LYNES, AMY DANIELLE (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2019)
As will be discussed in the introduction, the control and tuning of the self-assembly of supramolecular soft materials is an area of great current interest and importance. A particularly interesting motif for investigating what governs these processes is the BTA central unit decorated with a variety of different side arm functionalities. The aim of this PhD thesis was to investigate the role of side arm functionality on self-assembly processes and to study the soft materials formed from these various derivatives. Also discussed will be the structural studies of a series of pyridine-3,5-dicarboxamides. Chapter 2 will discuss the synthesis and characterisation of a family of short alkyl chain ester and carboxylic acid BTA derivatives. Investigations into the soft materials formed by these compounds will also be discussed. Chapter 3 will focus mainly on two BTA derivatives and their potential as porous materials. Briefly discussed will be the attempts to further extend the aromatic BTA derivative with some simple amino acids. Chapter 4 will introduce attempts to synthesise BTA-based polymers, both covalently and non-covalently linked, with a variety of side chains. Chapter 5 will first introduce a new central core unit, the pyridine-3,5-dicarboxylic acid unit and discuss some related example from the Gunnlaugsson group, followed by the synthesis and characterisation of a number of new derivatives. The chapter will then discuss the structural, microscopic and thermal studies of the materials formed from these derivatives. Chapter 6 contains the instrumental and experimental details, followed by the references and additional information, such as characterisation and supplementary data in the appendix.
APPROVED
Keywords: Supramolecular chemistry; Gels; Coordination polymers; Porous materials